Mainstreaming Waqf as a Source of Funding for Education at State Islamic Higher Education Institutions - Suradi Suradi; Hery Noer Aly; Mawardi Lubis; Iwan Romadhan Sitorus (Rumah Moderasi Beragama of UIN Siber Syekh Nurjati Cirebon, 2026)
Purpose ̶ This article aims to analyze the financing conditions of PTKIN and to propose a model for mainstreaming waqf as a sustainable source of educational funding. Design/methods/approach ̶ Employing a qualitative approach through literature review and policy document analysis, this study examines regulations on waqf, Islamic higher education financing policies, and existing practices of educational waqf management. Data were analyzed using thematic analysis and conceptual synthesis. Findings ̶ The findings suggest that mainstreaming waqf provides a sustainable alternative for financing PTKIN through policy integration, institutional strengthening, and productive waqf management. This approach enhances institutional financial independence while supporting the long-term development of endowment-based Islamic higher education financing. Conclusion ̶ This study proposes a mainstreaming waqf model based on three interrelated pillars: policy integration within PTKIN financing systems, strengthening professional and accountable waqf institutions, and developing productive waqf oriented toward educational endowment funds. Research Implication ̶ The study contributes to Islamic education financing discourse by positioning waqf as a strategic and sustainable institutional funding instrument.